Terpenoids from quinoa reverse chemoresistance in breast cancer by suppressing the stemness‐related lncRNA 667012 - Xiaxia Fan; Mangmang Feng; Dan Guo; Songtao Li; Yuxuan An; Jinmiao Tian; Zhuoyu Li (Food Frontiers)
Abstract Chemoresistance is a major cause of breast cancer (BC) recurrence and metastasis, and chemotherapy resistance comes from tumor stemness. Our previous study showed that quinoa bran terpenoids (QBT) exhibited significant antitumor activity. In this study, we found that QBT increased the sensitivity of drug‐resistant BC cells to the chemotherapeutic drugs adriamycin (ADR) and taxol (TAX). A novel lncRNA 667012 was identified along with QBT treatment. Moreover, overexpression of lncRNA 667012 promoted drug resistance, and the reduction of 667012 restored the drug sensitivity of resistant BC cells. More importantly, the findings revealed that lncRNA 667012 promoted stemness maintenance via the stemness‐related Wnt pathway. Furthermore, the result showed that QBT reduced 667012 expression and inhibited the activation of β‐catenin, thereby attenuating the stemness characteristics of BC and enhancing chemosensitivity. Consistently, the data were confirmed in the xenograft mice model. These results suggest that QBT could reverse chemoresistance by inhibiting stemness. It has the potential to be developed as a novel chemotherapeutic agent or chemosensitizer for BC treatment.